Effects of genetic background, sex, and age on murine atrial electrophysiology. Issue 6 (19th January 2021) - Obergassel, Julius; O'Reilly, Molly; Sommerfeld, Laura C; Kabir, S Nashitha; O'Shea, Christopher; Syeda, Fahima; Eckardt, Lars; Kirchhof, Paulus; Fabritz, Larissa
Abstract: Aims: Genetically altered mice are powerful models to investigate mechanisms of atrial arrhythmias, but normal ranges for murine atrial electrophysiology have not been robustly characterized. Methods and results: We analyzed results from 221 electrophysiological (EP) studies in isolated, Langendorff-perfused hearts of wildtype mice (114 female, 107 male) from 2.5 to 17.7 months (mean 7 months) with different genetic backgrounds (C57BL/6, FVB/N, MF1, 129/Sv, Swiss agouti). Left atrial monophasic action potential duration (LA-APD), interatrial activation time (IA-AT), and atrial effective refractory period (ERP) were summarized at different pacing cycle lengths (PCLs). Factors influencing atrial electrophysiology including genetic background, sex, and age were determined. LA-APD70 was 18 ± 0.5 ms, atrial ERP was 27 ± 0.8 ms, and IA-AT was 17 ± 0.5 ms at 100 ms PCL. LA-APD was longer with longer PCL (+17% from 80 to 120 ms PCL for APD70), while IA-AT decreased (−7% from 80 to 120 ms PCL). Female sex was associated with longer ERP (+14% vs. males). Genetic background influenced atrial electrophysiology: LA-APD70 (−20% vs. average) and atrial ERP (−25% vs. average) were shorter in Swiss agouti background compared to others. LA-APD70 (+25% vs. average) and IA-AT (+44% vs. average) were longer in 129/Sv mice. Atrial ERP was longer in FVB/N (+34% vs. average) and in younger experimental groups below 6 months of age. Conclusion: This work defines normal ranges for murine atrial EP parameters. Genetic background has a profound effect on these parameters, at least of the magnitude as those of sex and age. These results can inform the experimental design and interpretation of murine atrial electrophysiology. Graphical Abstract: